Design and Implementation of a Web-Based Personnel Information System (Sisfopers) At Kogartap II/Bandung - Rahmi Putri; Yusuf Andika; Debi Irawan; Hardiansyah Hardiansyah; Ismail Ismail (Brilliance: Research of Artificial Intelligence, 2025)
Personnel data management in the military is a crucial aspect in supporting the operational effectiveness of units. This study aims to design and implement a web-based Personnel Information System (Sisfopers) at Kogartap II/Bandung to make data management more efficient, secure, and integrated with the existing military IT infrastructure. The research method employed is developmental research (R&D) with a qualitative-descriptive approach, supplemented by data collection through literature review, observation, interviews, and documentation. The system is developed using the SDLC (Waterfall) model and UML to model functional requirements and process flows. The results indicate that the developed Sisfopers can accelerate administrative processes, maintain the security and integrity of personnel data, and support data-driven decision-making by the leadership. This study is expected to serve as a reference for the development of personnel information systems in other military environments